The Decentralized Central Bank: A Review Essay on The Power and Independence of the Federal Reserve by Peter Conti-Brown - Kocherlakota, Narayana R. (Journal of Economic Literature, 2017)
This essay discusses the structure and governance of the Federal Reserve System in light of the many changes in its activities over the past thirty years. Based on this analysis, it argues in favor of four specific reforms: clarification of Congressional expectations for the system; enhanced Federal Reserve Board of Governors transparency with respect to its oversight of the Reserve Banks; stripping monetary-policy votes from the President of the Federal Reserve Bank of New York and the Boards of Directors of the Reserve Banks; and the initiation of a public conversation about redesigning the Federal Reserve as a unified public entity. (JEL D72, E44, E52, E58, G21, G28)